Effectiveness of VIO-ASI (oxytocin massage animation video) on maternal and paternal breastfeeding self-efficacy: A quasi-experimental study - Eko Mardiyaningsih; Yuliaji Siswanto; Fiki Wijayanti (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2026)
Background: Exclusive breastfeeding remains a major public health priority, yet mothers who deliver by caesarean section often face early physiological and psychological barriers that may reduce breastfeeding confidence and limit effective family support. Objectives: This study evaluated the effectiveness of VIO-ASI, an oxytocin massage animation video, in improving maternal breastfeeding self-efficacy and paternal self-efficacy in supporting breastfeeding among post-caesarean families. Methods: A quasi-experimental pretest-posttest study with a control group was conducted in a general hospital in Central Java, Indonesia, from December 2025 to February 2026. The final sample comprised 32 mother-father pairs, including 17 in the intervention group and 15 in the control group. The intervention group received animated video on oxytocin massage, whereas the control group received standard hospital care. Maternal breastfeeding self-efficacy and paternal self-efficacy were measured at baseline and one week later using validated Indonesian instruments. Results: The intervention did not produce a statistically significant increase in self-efficacy among either mothers or fathers within one week. Maternal baseline self-efficacy was significantly lower in the intervention group than in the control group (56.29 ± 9.83 vs 63.47 ± 5.71; p=0.021). At follow-up, maternal scores remained lower in the intervention group, but the difference was no longer significant (56.41 ± 10.47 vs 60.93 ± 7.80; p=0.181). Within-group changes were not significant in either mothers (p=0.924 intervention; p=0.116 control) or fathers. For fathers, baseline scores were 58.24 ± 8.00 versus 61.07 ± 9.12 (p=0.272), and follow-up scores were 59.41 ± 8.47 versus 61.60 ± 7.63 (p=0.594), with no significant difference in change scores (p=0.815). Conclusions: animated breastfeeding education may be more useful as a supportive component within a broader postpartum lactation intervention than as an isolated educational tool. The findings highlight the importance of integrating digital education with counselling, demonstration, family participation, and postpartum follow-up.